Language Technology on News Portals - Ljubešić, Nikola, informatičar (Array, 2009)
In our research we analyzed the usage of language technology on five most popular Croatian news portals concerning morphological normalization for searching enhancement and content analysis for browsing enhancement. Since no language technology is used on any of these portals, we have developed and evaluated simple methods that can significantly enhance searching via stemming (prior F1 46.86, posterior F1 87.49%) and browsing news portals content via event detection (F0.5 81.2%).